Skills and politics. General and specific - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2011)
Skills and skill formation have become central topics in contemporary political economy. This essay traces a key concept in the current debate - the distinction between general and specific skills - back to its diverse origins in American postwar labor economics, comparative industrial relations, and human capital theory. To show how the distinction has evolved over time and between disciplines, it is related to other dual classifications of work skills, like high versus low, broad versus narrow, theoretical versus experiential, professional versus occupational, explicit versus tacit, extrafunctional versus functional, and certifiable versus noncertifiable. The aim is to reconstruct how notions of skill generality and skill specificity came to be used as the foundation of an economistic-functionalist 'production regime,' 'varieties of capitalism,' or 'asset' theory of welfare state development, and generally of politics under capitalism. – – Berufliche Qualifikationen und berufliche Bildung sind ein zentrales Thema gegenwärtiger politisch-ökonomischer Forschung. Der Aufsatz untersucht einen Schlüsselbegriff der Diskussion - die Unterscheidung zwischen allgemeinen und spezialisierten Fähigkeiten - mit Hinblick auf seine diversen Ursprünge in der amerikanischen Arbeitsökonomie der Nachkriegsjahre, der vergleichenden Forschung über industrielle Arbeitsbeziehungen und der Humankapitaltheorie. Um zu zeigen, wie die Begriffsbildung sich mit der Zeit und zwischen den verschiedenen Disziplinen entwickelt hat, wird sie mit anderen dualen Klassifikationen von beruflichen Fertigkeiten - hoch und niedrig, breit und eng, theoretisch und erfahrungsbasiert, explizit und implizit, extrafunktional und funktional, zertifizierbar und nicht zertifizierbar - in Beziehung gesetzt. Ziel ist herauszuarbeiten, wie die Unterscheidung zwischen allgemeinen und speziellen Qualifikationen zur Grundlage diverser ökonomistisch-funktionalistischer Theorien der wohlfahrtsstaatlichen Entwicklung und allgemein der Politik im Kapitalismus werden konnte.
Keywords: 300